2003
DOI: 10.1590/s1516-35982003000600012
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de energia no desempenho e características da carcaça de cordeiros alimentados em creep feeding

Abstract: RESUMO -O trabalho foi realizado no Setor de Ovinocultura da Universidade de Marília, objetivando estudar os efeitos de três níveis de energia (2,6; 2,8 e 3,0 Mcal EM/kg MS) na ração de cordeiros inteiros Suffolk criados em creep feeding, sobre o desempenho e características de carcaça. Na parição numerava-se e registravam-se o peso ao nascer dos cordeiros que, posteriormente, foram distribuídos aleatoriamente, compondo doze repetições por tratamento. As rações foram isoprotéicas (18,46% PB) fornecidas ad libi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
3
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 12 publications
2
11
3
10
Order By: Relevance
“…Similar results were also reported by Garcia et al (2003), who evaluated the productive performance and carcass traits of lambs receiving increasing energy levels in creep feed rations.…”
Section: Resultssupporting
confidence: 87%
“…Similar results were also reported by Garcia et al (2003), who evaluated the productive performance and carcass traits of lambs receiving increasing energy levels in creep feed rations.…”
Section: Resultssupporting
confidence: 87%
“…Rib yield was similar to that acquired by Zundt et al (2006), with Santa Inês lambs (8.27%), and average rib weight (0.66 kg) was superior to that obtained by Garcia et al (2003), of 0.37 kg.…”
Section: Resultssupporting
confidence: 85%
“…Gunn et al (2010a;2010b), when feeding sheep with 0 to 45% or 0 to 20% glycerin in the diet, respectively, did not find any effect of glycerin on loin eye area, having reported the values of 17.2 to 20.5 cm 2 . In this study, the longest and shortest loin lengths were superior to those found by Garcia et al (2003), who worked with crossbreed lambs slaughtered at 31 kg, and observed 53.2 mm for longest loin length and 28.6 mm for shortest loin length.…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…Esperava-se, no entanto, que o ganho médio diário dos cordeiros apresentasse comportamento linear positivo e influenciasse também o comportamento da idade ao abate, em virtude dos níveis crescentes, tanto de proteína bruta quanto de energia metabolizável (Tabela 1), como observado por Garcia et al (2003a) ao avaliarem diversos níveis de energia (2,60; 2,80 e 3,00 Mcal/kg MS) na ração de cordeiros Suffolk com acesso a cocho privativo. O resultado obtido neste trabalho pode estar relacionado ao fato de as fontes protéicas e energéticas serem, em boa parte, de suplementos alimentares diferentes, o que resultou em eficiência alimentar.…”
Section: Resultsunclassified